Changes in Medicago truncatula seed proteome along the rehydration–dehydration cycle highlight new players in the genotoxic stress response - Pagano, Andrea; Kunz, Laura; Dittmann, Antje; Araújo, Susana De Sousa; Macovei, Anca; Shridhar Gaonkar, Shraddha; Sincinelli, Federico; Wazeer, Hisham; Balestrazzi, Alma (Frontiers in Plant Science, 2023)
Using discovery mass spectrometry and label-free quantification, changes in the seed proteome of the model legume Medicago truncatula were investigated along the rehydration-dehydration cycle of a standard vigorization treatment (hydropriming plus dry-back) and during post-priming imbibition. From 2056 to 2190 proteins were detected in each pairwise comparison, among which six were differentially accumulated and 36 were detected only in one condition. The following proteins were selected for further investigation, as potential hallmarks of seed quality: MtDRP2B (DYNAMIN-RELATED PROTEIN), MtTRXm4 (THIOREDOXIN m4), and MtASPG1 (ASPARTIC PROTEASE IN GUARD CELL 1) showing changes in seeds under dehydration stress; MtITPA (INOSINE TRIPHOSPHATE PYROPHOSPHORYLASE), MtABA2 (ABSCISIC ACID DEFICIENT 2), MtRS2Z32 (SERINE/ARGININE-RICH SPLICING FACTOR RS2Z32), and MtAQR (RNA HELICASE AQUARIUS) that were differentially regulated during post-priming imbibition. For each candidate protein, changes in the corresponding transcript levels were assessed by qRT-PCR. Results highlighted the potential of the tested genes as indicators of the seed response to priming. Since in animal cells ITPA hydrolyses 2’-deoxyinosine triphosphate and other inosine nucleotides preventing genotoxic damage, a proof of concept was performed by imbibing primed and control M. truncatula seeds in presence/absence of 20 mM 2’-deoxyinosine. Results from comet assay highlighted the ability of primed seeds to cope with genotoxic damage induced by 2’-deoxyinosine. The seed repair response was assessed by monitoring the expression profiles of MtAAG (ALKYL-ADENINE DNA GLYCOSILASE) and MtEndoV (ENDONUCLEASE V) genes involved in the repair of the mismatched I :T pair, in the context of base excision reapair (BER) and alternative excision repair (AER) pathways, respectively.